Perencanaan Kawasan Permukiman Tranmigrasi Lahan Gambut Di Lokasi Muara Dadahup Propinsi Kalimantan Tengan - Perpustakaan UGM, i-lib ([Yogyakarta] : Fakultas Ekonomi,UGM, 1997)
A part of the national move towards rice self sufficiency in Indonesia is the development of one million hectares of peat land in Central Kalimantan. To this end, it is necessary to conduct a feasibility study of this area to ensure that it adheres to with the purpose and goals of development of Central Kalimantan. Following study of social, economic, physical, and environmental aspects in Muara Dadahup, this area is recommended as suitable for development as transmigration settlement area, supporting development of one milion hectares for cultivation of staple crops in Central Kalimantan. This research reveals that the Muara Dadahup area could be developed into four development areas (SKP), comprising 23 transmigration settlements (SP), which can be occupied by Â± 9,852 transmigrant households.